O efeito do exercício físico agudo com e sem suplementação aguda de cafeína sobre distintos domínios de funções executivas - Silva, Vander Pereira [UNIFESP] (2019)
Executive function is an umbrella term related to various aspects of quality of life that encompasses a series of correlated but dissociable cognitive processes that are related to the concept of attention and that allow the control of the behavior directed to a given goal. Research has pointed out that executive functioning can be improved by acute manipulations of physical activity and administration of caffeine. However, it is not clear what kind of executive function is favored by these manipulations are summative or synergistic., nor whether these effects occur together. The present study aimed to investigate the acute effects of physical activity (predominantly aerobic exercise [proof counter on a stationary, bicycle]) in combination with acute caffeine intake (6 mg / kg) in improving performance in three experimentally dissociable executive domains (inhibition, update and shifting) evaluated in two tasks: Random Number Generation – RNG, and Plus Minus Task. The sample consisted of 10 healthy young male volunteers, random order to two different conditions: acute physical exercise plus placebo or acute physical exercise plus caffeine. The executive performance was assessed before and after acute exercise combined with caffeine and placebo treatment. Regarding treatment administration, the study followed a double-blind, cross-over design. It was also evaluated the perception effort (Borg Scale) fatigue (Subjective Exercise Experiences Scale, SEES) and pain induced by exercise (Numeric Pain Rating Scale, NPRS) combined or not with caffeine. It was found that the exercise had a positive effect only on the executive domain of inhibition. The perception of exertion, fatigue and pain increased after exercise, and caffeine blocked post-exercise pain, although this treatment did not have an additional effect on exercise in any executive domain. Caffeine combined with exercise did not increase the effect of exercise on executive performance. It is concluded that the predominantly acute aerobic exercise exerts a positive effect on the executive domain of inhibition and that although the administered caffeine dose blocks the pain 30 minutes after the exercise, it has no nootropic effect on the executive functions.